Responsibility of Notary/Land Deed Official on Joint Title Deed Based on Incompatible Inheritance Certificate - Shintia Paramitha Dewi (Authentica, 2022)
This article aims to know how the Land Deed Official’s (In Indonesia: PPAT) responsibility for the incompatible inheritance statement was made. The Land Deed Official has the authority to make a deed based on the legal basis of Article 7 paragraph (1) Government  No. 24/2016 amending Government No.37/1998 concerning the Regulation of the Position of Land Deed Officials. Some people are dishonest in telling the truth about the administrative requirements, causing losses to several parties. This study uses a normative juridical method by conducting a literature study. The data used in this article are primary legal materials, secondary legal materials, and tertiary legal materials. The results of the study carried out are that a notary/Land Deed Official must be willing to make improvements if it is known that the inheritance information that has been made is not following what it should be. If the Notary/ Land Deed Official is not willing to revoke it, then the revocation can be done by filing a lawsuit against the Notary/Land Deed Official. When it is known that the court's decision has permanent legal force, the Notary/ Land Deed Official can be held civilly responsible by making compensation, costs, or interest if the deed made causes losses to several parties. The involvement of cooperation indicators in falsifying the deed, even the sale and purchase of the deed with the realization that there is inappropriate information, the Notary/ Land Deed Official can be criminally responsible. It can be concluded that the Notary/ Land Deed Official is responsible for the originality of the deed he/she made, including in making the Certificate of Inheritance. Keywords: Information doesn’t match; inheritance; Notary; Land Deed Official.